(untitled) (MMIT Proceedings, 2025)
The article discusses the possibilities of applying the STEAM approach in the process of teaching management disciplines in order to form students’ practice-oriented management competencies. Specific examples of using the STEAM approach in teaching management, human resources management, and marketing are presented.